Eccentric Ergometer Training Promotes Locomotor Muscle Strength but Not Mitochondrial Adaptation in Patients with Severe Chronic Obstructive Pulmonary Disease - MacMillan, Norah J.; Kapchinsky, Sophia; Konokhova, Yana; Gouspillou, Gilles; de Sousa Sena, Riany; Jagoe, R Thomas; Baril, Jacinthe; Carver, Tamara E.; Andersen, Ross E.; Richard, Ruddy; Perrault, Hélène; Bourbeau, Jean; et al. (Frontiers in Physiology, 2017)
Eccentric ergometer training (EET) is increasingly being proposed as a therapeutic strategy to improve skeletal muscle strength in various cardiorespiratory diseases, due to the principle that lengthening muscle actions lead to high force-generating capacity at low cardiopulmonary load. One clinical population that may particularly benefit from this strategy is chronic obstructive pulmonary disease (COPD), as ventilatory constraints and locomotor muscle dysfunction often limit efficacy of conventional exercise rehabilitation in patients with severe disease. While the feasibility of EET for COPD has been established, the nature and extent of adaptation within COPD muscle is unknown. The aim of this study was therefore to characterize the locomotor muscle adaptations to EET in patients with severe COPD, and compare them with adaptations gained through conventional concentric ergometer training (CET). Male patients were randomized to either EET (n=8) or CET (n=7) for 10 weeks and matched for heart rate intensity. EET patients trained on average at a workload that was three times that of CET, at a lower perception of leg fatigue and dyspnea. EET led to increases in isometric peak strength and relative thigh mass (p<0.01) whereas CET had no such effect. However EET did not result in fiber hypertrophy, as morphometric analysis of muscle biopsies showed no increase in mean fiber cross-sectional area (p=0.82), with variability in the direction and magnitude of fiber-type responses (20% increase in Type 1, p=0.18; 4% decrease in Type 2a, p=0.37) compared to CET (26% increase in Type 1, p=0.04; 15% increase in Type 2a, p=0.09). EET had no impact on mitochondrial adaptation, as revealed by lack of change in markers of mitochondrial biogenesis, content and respiration, which contrasted to improvements (p<0.05) within CET muscle. While future study is needed to more definitively determine the effects of EET on fiber hypertrophy and associated underlying molecular signaling pathways in COPD locomotor muscle, our findings promote the implementation of this strategy to improve muscle strength. Furthermore, contrasting mitochondrial adaptations suggest evaluation of a sequential paradigm of eccentric followed by concentric cycling as a means of augmenting the training response and attenuating skeletal muscle dysfunction in patients with advanced COPD.